Optimizing the Use of Simulation Technology in Digital Learning Content Development - Siregar, Isrina; Rofii, Agus; Kamal, Dianta Mustofa; Buka, Sisilia Prima Yanuaria; Xavier, Murphy; Elliot, McCarty (Journal International Inspire Education Technology, 2023)
Education in the era of globalization that allows no limits to find all information is very easy and effective to do anywhere. By utilizing simulation technology in learning so that you can prepare even better. Of course there are stages that must be followed, such as knowing what positive effects are applied using simulation technology for the development of digital learning content, you have to know the methods with people who are experienced and knowledgeable in the field. By utilizing this technology in the form of digital learning content that is able to create effective and quality learning, so that it can make the next generation superior and competitive. Increasingly sophisticated technology can facilitate human work in all fields, especially in the field of education. Many people are competing to create interactive media, so they can earn from the media they create. This should also receive attention from parties related to the world of education. The method used in this study is a quantitative method by distributing a questionnaire containing 15 statements about this simulation technology for digital learning. The purpose of this research is to optimize the use of simulation technology to enhance digital learning for students so they are able to master the skills to use maximally, creatively and innovatively against this limitless technological development. The conclusion from this study is that technology greatly influences student learning development, one of which is by optimizing the use of simulation technology in digital learning. Students and teachers really get a big positive impact with the presence of this sophisticated tool. The limitation of this research is that researchers only conduct research at the school or madradah level, which in fact they need learning media like this in learning in class, so that the class atmosphere is more conducive and attracts students' attention to learning with focus.